Solovyov : Chaos and All-unity - Drozdek, Adam (Laval théologique et philosophique)

(untitled) (Faculté de philosophie, Université Laval, 2009)
The paper discusses several issues of Solovyov’s ontology and theology including the metaphysics of all-unity ; original but contentious doctrine of creation ; the problem of the Fall and the restoration of all-unity ; the problem of the omnipresence of consciousness.